Efektivitas Edukasi Berbasis Multimedia dan Suplementasi Zat Besi terhadap Pengetahuan Anemia dan Kadar Hemoglobin pada Santri Perempuan Kelas VII di SMP Nurul Jadid - Dwi Lestari, Yusri; Ahmad Kholid Fauzi (Jurnal Medicare, 2025)
Anemia is one of the common health problems affecting adolescent girls, including those in Islamic boarding school (pesantren) environments, which have distinctive lifestyle and learning patterns. Low levels of knowledge and poor adherence to iron supplementation are major contributors to the high prevalence of anemia in this population. This study aimed to analyze the effectiveness of animation-based education and iron tablet supplementation on improving knowledge and hemoglobin levels among seventh-grade female students at SMP Nurul Jadid. A quasi-experimental design with a pretest-posttest approach without a control group was used, involving 45 students selected from one of five classes through purposive sampling. The intervention consisted of educational sessions using animated videos covering topics on adolescent nutrition, anemia, and the importance of iron tablet consumption, alongside the provision of one iron tablet per week over a six-month period. Data were collected through a knowledge questionnaire and hemoglobin measurements before and after the intervention, and analyzed using a paired t-test. The results showed a significant improvement in both knowledge (p = 0.001) and hemoglobin levels (p = 0.002). Therefore, animation-based education combined with iron tablet supplementation is proven effective in enhancing nutritional and anemia-related knowledge and in increasing hemoglobin levels among adolescent girls.